2013
DOI: 10.1039/c2em30731f
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular conversion of silver ions into silver nanoparticles by protozoan Tetrahymena thermophila

Abstract: In the current study, cell-free exudates of the ciliated protozoan Tetrahymena thermophila were shown to progressively convert silver nitrate to silver nanoparticles (Ag NPs) under illumination at ambient temperature. The formation of Ag NPs in the reaction mixture was evidenced by gradual colour changes, appearance of a specific absorbance peak (420–450 nm) and visualization using scanning electron microscopy coupled to an energy-dispersive X-ray spectrometer. After 2 h of incubation the mean hydrodynamic siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…139, 140 Assessment outcomes are affected by media chemistry, physical characteristics, and additives (e.g., soil pH, 141 temperature, 142 or organic matter content, 108, 143 and dispersing agents in aqueous media 144 ). The exposure concentration at the receptor and consequent effects 145 depend on ENM dissolution 146 perhaps assisted by biotic ligands, 147 and speciation, 103 shed ions, 103 surface associations, 148 and heteroaggregation with colloids and particulate matter, 148-151 or agglomeration and settling. 152 All of these vary with ENM types and their varying properties, and ambient conditions.…”
Section: What Exposure Conditions Are Used In Assessing Enm Ecologicamentioning
confidence: 99%
“…139, 140 Assessment outcomes are affected by media chemistry, physical characteristics, and additives (e.g., soil pH, 141 temperature, 142 or organic matter content, 108, 143 and dispersing agents in aqueous media 144 ). The exposure concentration at the receptor and consequent effects 145 depend on ENM dissolution 146 perhaps assisted by biotic ligands, 147 and speciation, 103 shed ions, 103 surface associations, 148 and heteroaggregation with colloids and particulate matter, 148-151 or agglomeration and settling. 152 All of these vary with ENM types and their varying properties, and ambient conditions.…”
Section: What Exposure Conditions Are Used In Assessing Enm Ecologicamentioning
confidence: 99%
“…While after a decade-long research the exact mechanisms of toxic action of ENMs are still debated, the main proposed mechanisms can be outlined as follows: (i) physical interactions of ENMs with cells or cellular components, (ii) production of reactive oxygen species and resulting induction of oxidative stress, and (iii) toxic effect of released ions from metal/metal oxide ENMs [13,25,28]. Analyses of the information in NanoE-Tox database (Table S2, Supporting Information File 1) revealed that the most often reported potential mechanism of toxic action for ZnO [128][129][130][131][132]173], Ag [44,[64][65][66][67][68][69][70][71][72][73][174][175][176][177], and CuO [55,64,73,[126][127][128][129]173] NPs was the release of metal ions. On the other hand, some studies have also proposed that the toxicity of these ENMs might be at least partially caused by the NPs themselves [73][74][75][76][77][78][79][80][81][82]…”
Section: Mechanism Of Toxic Actionmentioning
confidence: 99%
“…Such detoxification strategies are not confined to prokaryotic microorganisms. Juganson et al 98 showed that the extracellular soluble fraction of protozoa Tetrahymena thermophila contained potent Ag + -reducing substances that contributed to the formation of AgNPs – less toxic form of silver to protozoa – from AgNO 3 . While the carbohydrates of EPS might be responsible for the reduction of Ag + to metallic silver, soluble proteins were shown to play a role in the formation and stabilization of AgNPs by rendering a protein corona on the NPs.…”
Section: Np-biomolecular Interactions In Nanotoxicology a Frontiermentioning
confidence: 99%